Targeting the Hedgehog Pathway Using Itraconazole to Prevent Progression of Barrett's Esophagus to Invasive Esophageal Adenocarcinoma. Issue 6 (June 2021) - Kelly, Ronan J.; Ansari, Amir M.; Miyashita, Tomoharu; Zahurak, Marianna; Lay, Frank; Ahmed, A. Karim; Born, Louis J.; Pezhouh, Maryam K.; Salimian, Kevan J.; Ng, Christopher; Matsangos, Aerielle E.; Stricker-Krongrad, Anne-Heloise; et al.
Abstract : Objective: The aim of the study was to investigate whether inhibition of Sonic Hedgehog (SHH) pathway would prevent progression of Barrett's Esophagus (BE) to esophageal adenocarcinoma. Background: The hedgehog signaling pathway is a leading candidate as a molecular mediator of BE and esophageal adenocarcinoma (EAC). Repurposed use of existing off-patent, safe and tolerable drugs that can inhibit hedgehog, such as itraconazole, could prevent progression of BE to EAC. Methods: The efficacy of itraconazole was investigated using a surgical rat reflux model of Barrett's Metaplasia (BM). Weekly intraperitoneal injections of saline (control group) or itraconazole (treatment group; 200 mg/kg) were started at 24 weeks postsurgery. Esophageal tissue was harvested at 40 weeks. The role of the Hh pathway was also evaluated clinically. Esophageal tissue was harvested after 40 weeks for pathological examination and evaluation of the SHH pathway by immunohistochemistry. Results: BM was present in control animals 29 of 31 (93%) versus itraconazole 22 of 24 (91%). EAC was significantly lower in itraconazole 2 of 24 (8%) versus control 10 of 31 (32%), respectively ( P = 0.033). Esophageal SHH levels were lower in itraconazole vs control ( P = 0.12). In esophageal tissue from humans with recurrent or persistent dysplastic BE within 24 months of ablative treatment, strong SHH and Indian Hedgehog expression occurred in distal BE versus proximal squamous epithelium, odds ratio = 6.1 (95% confidence interval: 1.6, 23.4) and odds ratio = 6.4 (95% confidence interval: 1.2, 32.8), respectively. Conclusion: Itraconazole significantly decreases EAC development and SHH expression in a preclinical animal model of BM. In humans, BE tissue expresses higher SHH, Indian Hedgehog, and bone morphogenic protein levels than normal squamous esophageal epithelium.